The lime botany, production and uses - Khan, M. Mumtaz; Al-Yahyai, Rashid (Rashid Abdullah), 1971-; Al-Yahyai, Fahad (CABI, 2017)
This book is the most recent collection of research and scientific literature exclusively dedicated to lime (Rutaceae) culture and the marketplace. The coverage of each subject area is broad, ranging from basic cultivation practices to postharvest handling to uses, which makes it the best choice for amateurs and professionals alike. Chapter 1 emphasizes lime importance and global production, while chapter 2 covers its comprehensive systematic classification and distribution. In chapter 3, lime breeding, genetics and biodiversity are discussed; and in chapter 4, lime tree growth, development and reproductive physiology are elaborated. In chapter 5, propagation techniques, nursery production and certification are explained, while in chapter 6, schematic planning for lime orchard establishment is discussed. In chapter 7, crop water requirements, irrigation systems and fertigation are highlighted; and in chapter 8, cultural practices, e.g. tree pruning, thinning, weeding, planting density and intercropping, are covered. In chapter 9, precision agriculture in lime is elaborated; and in chapter 10, insect pests and diseases and their control measures are covered. In chapter 11, innovative production technologies, e.g. the use of plant growth regulators, remote sensing and organic production systems, are highlighted. In Chapter 12, harvesting and postharvest management of lime fruit are emphasized; and in chapter 13, the uses (folk to modern) and future dynamics are discussed in depth. With the latest information presented in simple language, this book will appeal to a range of principal users, e.g. educators, researchers, students, agriculture extension workers, farming communities, industry personnel and professionals/practitioners